Enhancing Senior Students Critical Thinking Skills on Thermodynamics Topic Using Problem-Based Learning Integrated with STEM - Kholil, Abdullah; Supriana, Edi; Handayanto, Supriyono Koes (Universitas Negeri Malang, 2022)
This study aims to determine the improvement of students’ critical thinking skills related to the topic of thermodynamics which is taught using a stem-integrated problem-based learning model. The research subjects were 52 students of class XI MIPA 2 and XI MIPA 3 SMAN Pronojiwo. The research model used was explanatory methods. The results of this study indicated that the initial critical thinking ability of the control class students was higher than the experiment class, with medians of 8 and 6.5. After the intervention, the obtained median values of 10 and 10 with the Mann-Withney test P 0.05, signifying no difference after the intervention. In addition, students’ abilities in the category of problem-solving, hypothesizing, and reasoning abilities experienced positive changes.Keywords: Critical thinking skills, problem-solving, problem-based learning, STEM, thermodynamics ABSTRAKPenelitian ini bertujuan untuk mengetahui peningkatan kemampuan berpikir kritis terkait topik termodinamika yang diajarkan dengan menggunakan pembelajaran berbasis problem based learning terintegrasi STEM. Subjek pada penelitian ini adalah siswa pada kelas XI MIPA 2 dan XI MIPA 3 SMAN Pronojiwo sebanyak 52 anak. Desain Penelitian yang digunakan adalah Explanatory methods. Hasil penelitian ini menunjukkan kemampuan awal berpikir kritis siswa kelas konvensional lebih tinggi dari kelas permodelan dengan median 8 dan 6,5. Perubahan setelah intervensi perolehan nilai median sebesar 10 dan 10 dengan uji mann-withney P ≥ 0,05 menyatakan tidak ada perbedaan atau sama setelah intervensi. Selain itu kemampuan siswa mengalami perubahan yang positif pada rubrik kemampuan pemecahan masalah, berhipotesis dan penalaran.Kata Kunci: keterampilan berpikir kritis, pemecahan masalah, pembelajaran berbasis masalah, STEM, termodinamika